2011
DOI: 10.1021/je200373q
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Liquid Densities of n-Pentane, n-Octane, and n-Nonane and Their Binary Mixtures from (273.15 to 363.15) K at 0.1 MPa

Abstract: This paper presents experimental liquid densities for n-pentane, n-octane, and n-nonane and their binary mixtures from (273.15 to 363.15) K over the entire composition range (for the mixtures) at atmospheric pressure. The experimental apparatus is a vibrating-tube densimeter. It is possible to compare the results to a generalized correlation for liquid densities of n-alkanes and to molecular dynamics simulations. The average absolute percentage deviation is (0.06 and 0.8) % using the equation and the simulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…The experimental values of densities, viscosities, and refractive indices of the pure samples under different temperatures are compared with those from the references ,, in Table . The absolute average relative deviations (AARD) are calculated according to the following equation, and the results indicate that the experimental values agree well with the literature data. where P is the measurement data of density, viscosity, or refractive index in this work, and P lit is the literature data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental values of densities, viscosities, and refractive indices of the pure samples under different temperatures are compared with those from the references ,, in Table . The absolute average relative deviations (AARD) are calculated according to the following equation, and the results indicate that the experimental values agree well with the literature data. where P is the measurement data of density, viscosity, or refractive index in this work, and P lit is the literature data.…”
Section: Resultsmentioning
confidence: 99%
“… a Standard uncertainties u are u ( p ) = 0.50 kPa, u ( T ) = 0.01 K, u r (ρ) = 0.001, u r (η) = 0.02, and u c ( n D ) = 0.0005. b Ref . c Ref . d Ref . e Ref . f Ref . g Ref . h Ref . i Ref . j Ref . k Ref . l Ref . m Ref . n Ref . o Ref . p Ref . q Ref . r Ref . …”
Section: Resultsmentioning
confidence: 99%
“…Looi et al 2 measured both excess enthalpies and excess volumes for pseudohexadecane consisting of an equimolar mixture of tridecane + nonadecane and concluded that the principle held. A further application of the congruence principle is illustrated in the recent measurements of Ramos-Estrada et al 17 who reported density measurements on mixtures of pentane, octane, and nonane over a wide temperature range. The density data for mixtures at mole fractions corresponding to the intermediate pure alkanes show agreement with those pure alkanes almost within experimental uncertainty.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…For instance, liquid densities of pentane, octane and nonane, and of their binary mixtures were measured by Ramos-Estrada et al 261 from 273.15 K to 363.15 K at 0.1 MPa, using a vibrating-tube densimeter from Anton Paar (DMA 5000). Volumetric properties, i.e.…”
Section: Mixtures Of Aprotic Liquidsmentioning
confidence: 99%